2015
DOI: 10.1021/acs.joc.5b01264
|View full text |Cite
|
Sign up to set email alerts
|

Bastimolide A, a Potent Antimalarial Polyhydroxy Macrolide from the Marine Cyanobacterium Okeania hirsuta

Abstract: Bastimolide A (1), a polyhydroxy macrolide with a 40-membered ring, was isolated from a new genus of the tropical marine cyanobacterium Okeania hirsuta. This novel macrolide was defined by spectroscopy and chemical reactions to possess one 1,3-diol, one 1,3,5-triol, six 1,5-diols, and one tert-butyl group; however, the relationships of these moieties to one another were obscured by a highly degenerate (1)H NMR spectrum. Its complete structure and absolute configuration were therefore unambiguously determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 22 publications
0
75
0
1
Order By: Relevance
“…is free‐living and not known to be involved in symbiotic associations. Moreover, this characterization of the phormidolide PKS pathway as belonging to the trans ‐AT PKSs suggests that this type of pathway may be responsible for the formation of other cyanobacterial polyketides, such as oscillariolide, the caylobolides, and bastimolide …”
Section: Resultsmentioning
confidence: 88%
“…is free‐living and not known to be involved in symbiotic associations. Moreover, this characterization of the phormidolide PKS pathway as belonging to the trans ‐AT PKSs suggests that this type of pathway may be responsible for the formation of other cyanobacterial polyketides, such as oscillariolide, the caylobolides, and bastimolide …”
Section: Resultsmentioning
confidence: 88%
“…These MS/MS spectra did not match with any library entry upon molecular networking. However, they clustered together in a small molecular family, and upon library comparison with the analog search option, were suggested to be structurally related to a polyhydroxy macrolide, such as bastimolide A (Shao et al 2015). A number of minor metabolites were also detected in the chromatogram by MS or DAD UV, but were not analyzed further due to their low abundance.…”
Section: Resultsmentioning
confidence: 99%
“…However, the parent masses observed in this study were not found to correlate with any known molecules of this class in the MarinLit or Dictionary of Natural Products databases. Additionally, the molecular networking performed using GNPS failed to yield any matches against spectra present in the available MS/MS library databases for the four major metabolites present in the extract, but did suggest that these compounds could be analogs of the reported polyhydroxy macrolide natural product known as bastimolide A (Shao et al 2015). On the other hand, of the lower abundance molecules in the extract, it was possible to identify several known diketopiperazines.…”
Section: Discussionmentioning
confidence: 99%
“…Bastimolide A ( 50 ), isolated from the marine Okeania hirsuta from Bastimentos Park, Panama, is a rare 40-membered polyhydroxy macrolide consisting of one 1,3-diol, one 1,3,5-triol, six 1,5-diols and one tert -butyl group. Bastimolide A ( 50 ) exhibits strong cytotoxicity against Vero cells with an IC 50 value of 2.1 µM [31]. …”
Section: Anti-neoplastic Property Of Cyanobacterium-derived Macrolmentioning
confidence: 99%
“…It has been proven that bastimolide A ( 50 ) is a potentially promising antimalarial lead compound with high selectivity and antimalarial activity against drug-resistant strains [31]. Malyngolide dimer ( 58 ) was isolated from the marine cyanobacterium Lyngbya majuscula collected from Panama and was shown to exhibit moderate antimalarial activity against chloroquine-resistant Plasmodium falciparum (W2) with an IC 50 value of 19 µM [53].…”
Section: Other Bioactivitymentioning
confidence: 99%